Pengaruh Kompleksitas Perusahaan Fee Audit Going Concern Risk dan Spesialisasi Auditor terhadap Key Audit Matters (KAMs) - Muhammad Putra Ramadhan; Widya Rizki Eka Putri (AKUNTANSI 45, 2026)
This study aims to examine the influence of firm complexity, audit fees, going concern risk, and auditor specialization on key audit matters (KAMs). This study employs a multiple linier regression analysis using secondary data in the form of finansial statements and annual reports from companies in the non-essential consumer goods sector for the period 2022-2024. Firm complexity is proxied by the number of business segments, audit fees are measured using the natural logarithm of audit fees, going concern risk is proxied using a dummy variable, and auditor specialization is measured based on the proportion of industry clients handled by the auditor. The results indicate that firm complexity has a significant negative effect on key audit matters, audit fees have a significant positive effect on key audit matters, going concern risk has a non-significant negative effect on key audit matters, and auditor specialization has a non-significant positive effect on key audit matters. These findings indicate that the disclosure of key audit matters is more influenced by the scope of the audit and the auditor’s professional judgment in determining relevant audit issues to be disclosed to financial statement users.